Environmental sensitivity to assess suitability and susceptibility to soils east of Karbala - Shanishil, Zainab Sabah; Abood, Abdallah S. (Al-Adab Journal, 2022)
The aim of this study was to determine the suitability and susceptibility of agricultural lands to the east of Karbala soils for the cultivation of sensitive agricultural crops through the optimal use of modern geographic techniques (remote sensing and geographic information systems) in distributing and determining the suitability and susceptibility of lands and detecting the changes obtained. As the area of the study area reached (84,655 km2), the study relied on the natural and human data of the study area (such as the location, geological formation, climate and its characteristics, in revealing the extent of suitability and suitability of the soil. The study included levels in dividing the soil in the east of the governorate to reveal its sensitivity and its susceptibility to For production, it came with the followi First level of suitability for critical susceptibility, salt tolerant crops, level two, low suitability, sugar crops, level three, medium suitability, field crops, level four, suitability, vegetables, level five, high suitability, palm trees and fruit orchard The study suggests benefiting from modern geographical techniques in detecting and monitoring changes in vegetation cover and other land uses in another region